Econlit: A10; A13; E32. [en] Economic crisis and social economy - Manuel Jaén García (AECOOP Escuela de Estudios Cooperativos, 2018)
The economic recession of 2008 deeply impacted numerous sectors in the Spanish economy. Although this crisis was sparked by the housing bubble followed by the demise of a large part of now defunct savings banks, it spread throughout the entire economy leaving a trail of business closures and massive unemployment. In addition, after having bailed out the banks during the recession, the public sector was left with an enormous hole in public finances and an interest rate differential on debt payments (the so-called risk premium) that surpassed 500 basis points with respect to German debt. Intervention by the European Central Bank (ECB), which consisted of a massive purchase of sovereign debt, allowed the country, in part, to overcome this situation and foster a growing economy in recent years (2014 onwards). The present work is set within this context and studies the behavior of social enterprises during the crisis period in comparison with the economy in general. With this aim, the most common indicators are utilized and the two sectors are compared: the general business sector and the social enterprise sector in particular.